DISTANCE EDUCATION IN A HIGH SCHOOL EDUCATIONAL ACTIVITY: CHALLENGES OF TIME - YASHCHENKO, Eleonora; LEVANDOVSKA, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article notes that the modern transition of education from traditional to distance makes changes in the format of educational activities of higher education institutions. New methods and ways of its organization are introduced; teachers meet new requirements concerning the effective realization of their skills and the increase of their professional mobility. Updated tasks that require teachers training to use information technology in the professional activities of higher education institutions in the context of distance education are emphasized, especially: a) studying of the general principles of information technology, the development of teacher’s key level of information competence; b) mastering of the information technologies which are specific to the subject area that corresponds to the teacher’s specialty; c) knowing of general theory and methodology of information technology using in professional pedagogical activities; d) preparing for using in the process of teaching the information technology which is specially focused on a particular subject. There is a modular principle in the basis of distance learning programs, which means that each discipline consists of several independent learning modules (topics) due to its content. Accordingly, each discipline contains the following parts: content-related (electronic version of the lectures); training (practical classes); controlling (tests and creative tasks). At the same time, the teachers learn to effectively develop author's distance courses, to place teaching materials (lectures, tasks for practical / laboratory and independent work; additional materials, as well as video, audio and presentation materials in various formats and through additional plug-ins, to automatically generate tests, add new course resources). In this research it was revealed that scientific and pedagogical workers need to: form knowledge, skills and abilities in the field of network culture; teach students strategies and tactics of interaction with carriers and sources of new knowledge, master skills of two-side communication with a large number of users, whose activities are monitored and controlled; study new information technologies that are specific to the subject area that corresponds to teacher’s specialty; create space for improving their professional activities and developing innovative methods; develop varied methodology for distance learning of people with different levels of abilities, age and needs